Multi-Objective Optimization for Power Efficient Full-Duplex Wireless Communication Systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (Global Communications Conference (GLOBECOM), 2015)
In this paper, we investigate power efficient resource allocation algorithm design for multiuser wireless communication systems employing a full-duplex (FD) radio base station for serving multiple half-duplex (HD) downlink and uplink users simultaneously. We propose a multi-objective optimization framework for achieving two conflicting yet desirable system design objectives, i.e., total downlink transmit power minimization and total uplink transmit power minimization, while guaranteeing the quality-of-service of all users. To this end, the weighted Tchebycheff method is adopted to formulate a multi-objective optimization problem (MOOP). Although the considered MOOP is non-convex, we solve it optimally by semidefinite programming relaxation. Simulation results not only unveil the trade-off between the total downlink and the total uplink transmit power, but also confirm that the proposed FD system provides substantial power savings over traditional HD systems.
Keywords: Downlink; Uplink; Optimization; Resource Management; MIMO; Wireless communication; High definition video